In vitro model of human subcutaneous adipocyte spheroids for studying mitochondrial dysfunction and mitochondria activating compounds - Wagner, Anita; Lautaoja-Kivipelto, Juulia H.; Pehkonen, Kalle; Hassinen, Antti; Kuusela, Minna; Röttger, Lisa; Herbers, Elena; Ioannidou, Anna; Mädler, Sophia; Rothenaigner, Ina; Srinivasan, Soumya; Laasonen, Sini; et al. (Elsevier BV, 2026)
Mitochondrial abnormalities drive subcutaneous white adipose tissue dysfunction in obesity, yet in vitro models to study adipocyte mitochondria remain limited. Here, we establish a human subcutaneous adipocyte spheroid model to characterize mitochondrial metabolism under obesity-relevant conditions and drug exposure. Human preadipocyte spheroids were differentiated in ultra-low attachment plates for 3 weeks using thiazolidinedione-free medium. Matrigel embedding was incorporated into the protocol as it promoted mitochondrial network and respiration compared to scaffold-free conditions. Differentiated spheroids showed increased lipid accumulation, adipogenic gene expression, mitochondrial respiration, adiponectin secretion, and hormonal responsiveness. Lipid mixture administration during differentiation induced metabolic disturbances, including mitochondrial respiration failure, alongside increased mitochondrial biogenesis. Post-differentiation treatment with rosiglitazone, a peroxisome proliferator-activated receptor γ agonist, improved mitochondrial bioenergetics and adiponectin secretion in lipid mixture-administered adipocyte spheroids. Our model enables precise measurement of adipocyte mitochondria metabolism, providing a platform for mitochondria-focused research and drug discovery in obesity.